Pengukuran Tingkat Literasi Digital Masyarakat Kabupaten Sleman dalam Konteks Pengembangan Smart Regency (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The development of information and communication technology has driven digital transformation across various sectors, including local governments adopting the Smart Regency concept. Digital literacy plays a vital role in supporting the success of Smart Regency implementation, as it determines citizens’ ability to access, understand, and utilize technology effectively and safely. This study aims to measure the digital literacy level of Sleman Regency residents and analyze its contribution to Smart Regency development. The research employs a survey method by distributing questionnaires to residents in several areas of Sleman. The instrument was designed based on four dimensions of digital literacy: technological ability, digital security, problem-solving, and online communication and collaboration. Data were analyzed using descriptive quantitative techniques to illustrate digital literacy levels based on demographic factors and technology usage intensity. The results indicate that most Sleman residents possess a moderate level of digital literacy, with notable variations in digital security and online collaboration aspects. These findings provide implications for local governments to strengthen digital education programs and expand technology access as part of an inclusive and sustainable Smart Regency development strategy.